2016
DOI: 10.1016/j.jpba.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic interaction chromatography for the characterization of monoclonal antibodies and related products

Abstract: Hydrophobic interaction chromatography (HIC) is a historical strategy used for the analytical purification and characterization of proteins. Similarly to what can be done in reversed-phase liquid chromatography (RPLC), HIC is able to separate protein species based on their hydrophobicity, but using different conditions. Compared to RPLC, the main benefit of HIC is its ability to perform separations under non denaturing conditions (i.e. physiological pH conditions, ambient mobile phase temperature and no need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 85 publications
3
72
0
1
Order By: Relevance
“…Recent review papers detailed HIC method development and also showed some useful applications [22][23][24]. The goal of the present review was to summarize the main points of these works and complete them with most recent results.…”
Section: Hydrophobic Interaction Chromatography (Hic)mentioning
confidence: 99%
“…Recent review papers detailed HIC method development and also showed some useful applications [22][23][24]. The goal of the present review was to summarize the main points of these works and complete them with most recent results.…”
Section: Hydrophobic Interaction Chromatography (Hic)mentioning
confidence: 99%
“…Unlike RP, HIC operates under non denaturing conditions (no organic solvents, physiological pH, and ambient mobile phase temperature) and has shown success in separating charge variant species (Boyd, Kaschak, & Yan, ; Ouellette, Chumsae, Clabbers, Radziejewski, & Correia, ; Valliere‐Douglass, Wallace, & Balland, ). Recent improvements in the stationary phase for HIC have focused on decreasing particle size to enhance the kinetic performance, which may allow for greater industrial scale adoption (Fekete, Veuthey, Beck, & Guillarme, ).…”
Section: Principles Of Charge Variants Analyticsmentioning
confidence: 99%
“…Complete inactivation (Rehder et al, 2008) Succinimide Asn, Asp May illicit immune response (Chen et al, 1996) C-terminal Lys/Arg Lys, Arg No significant impact on binding, PK, or half-life (Alt et al, 2016;Antes et al, 2007;Khawli et al, 2010;Lyubarskaya et al, 2006) Ouellette, Chumsae, Clabbers, Radziejewski, & Correia, 2013;Valliere-Douglass, Wallace, & Balland, 2008). Recent improvements in the stationary phase for HIC have focused on decreasing particle size to enhance the kinetic performance, which may allow for greater industrial scale adoption (Fekete, Veuthey, Beck, & Guillarme, 2016). Table 2 shows selected representative works for analyzing charge variant species and the techniques used in those studies.…”
Section: Isomerization Aspmentioning
confidence: 99%
“…Rituximab (pI of ∼9.1) and panitumumab (pI of ∼6.7) are intended to represent basic and acidic mAbs, respectively [26]. Ipilimumab is hydrophobic, while denosumab can be considered as a relatively hydrophilic mAb [32]. NISTmAb is currently the only universal standard reference material (SRM) for monoclonal antibody therapeutics.…”
Section: Development Of a General Hilic Gradientmentioning
confidence: 99%